DESENVOLVIMENTO E VALIDAÇÃO DE MÉTODO ANALÍTICO PARA A DETERMINAÇÃO DE Ca, Cu, Fe, Mg, Mn e Zn POR FAAS EM FARINHAS DE MILHO PRODUZIDAS NO ESTADO DO PARANÁ - Kelte Filho, Irineo (2017)
Corn (Zea mays) is one of the most produced cereals in Brazil, being the State of Paraná the largest producer in the country. In addition to being a nutritious food, it is used in both, animal consumption and human consumption, in the in natura form or of “canjicas” or flours form. Corn flour is present in the preparation of several Brazilian dishes and it is highly consumed due to its affordable value. Despite of this, not many bibliographical references about the mineral composition of corn flour are found. In Brazil, the official method used for the preparation and determination of metals is described by the AOAC (Association of Official Analytical Chemists), the digestion being done by the dry ashing process, through the calcination of the samples at high temperatures, which can cause loss of analyte by volatilization, in addition to being a time-consuming and expensive process. Thus, it is necessary to search fast and cost-effective analytical methodologies for the determination of metal ions in corn flours. The objective of this work was to develop, optimize and validate an analytical methodology for the determination of Ca, Cu, Fe, Mg, Mn and Zn metal ions in samples of corn flour produced in the State of Paraná. In this work, the wet digestion of the samples was applied using HNO3, heating in a digester block and solubilization in an ultrasonic bath. The validation tests involved studies of linearity and working range, detection and quantification limits, accuracy and precision. The samples were digested with recuperation rates of 93% for Ca, 98% for Cu, 110% for Fe, 97% for Mg, 101% for Mn and 106% for Zn. Concentrations of Ca, Cu, Fe, Mg, Mn and Zn were determined in 23 samples of yellow corn flour and 11 samples of white flour. The averages of the concentrations determined for Ca, Cu, Fe, Mg, Mn and Zn in the yellow flours were 51.04; 0.49; 8.05; 81.45; 1.38 and 1.92 mg / kg, respectively, and 64.44; 0.57; 7.35; 98.44; 1.31 and 2.74 mg / kg in white flour, respectively. A Principal Component Analysis (PCA) suggested may be a correlation between the mineral contents and the places of origin of the flours. It was also evaluated the mineral contribution coming from the ingestion of the flour according to the criteria of RDI (Recommended Daily Intake).